2011
DOI: 10.1111/j.1469-0691.2010.03343.x
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide pseudo-outbreak of Salmonella enterica ssp. diarizonae, France

Abstract: To investigate an increased incidence of human cultures growing Salmonella enterica ssp. diarizonae serotype 61:k:1,5,7 in France in 2008, we reviewed medical records of case patients and identified the material used during invasive procedures and for bacterial culture. Trace-back investigations incriminated culture media containing contaminated sheep blood agar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Only a small number of severe human cases have been described, which mainly affected high-risk groups, such as infants [ 19 ], immunocompromised adults [ 20 ] and the elderly [ 21 ]. No larger outbreak of human infections with SASd has been documented so far and a pseudo-outbreak in France could be traced back to contaminated sheep blood agar [ 22 ]. Given the high prevalence of SASd in sheep and the low number of human infections, Swedish authorities have concluded that the risk management of this serovar in sheep can be exempted without any adverse effect on human health [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of severe human cases have been described, which mainly affected high-risk groups, such as infants [ 19 ], immunocompromised adults [ 20 ] and the elderly [ 21 ]. No larger outbreak of human infections with SASd has been documented so far and a pseudo-outbreak in France could be traced back to contaminated sheep blood agar [ 22 ]. Given the high prevalence of SASd in sheep and the low number of human infections, Swedish authorities have concluded that the risk management of this serovar in sheep can be exempted without any adverse effect on human health [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…After some investigations, they revealed that nine of the ten isolates had grown on sheep blood agar from the same manufacturer and that the batch number was similar for three cases. The manufacturer confirmed that the samples of the blood agar were positive to SED, owing to contaminated sheep blood [43].…”
Section: Zoonotic Potential Of Salmonella Enterica Subsp Diarizonae Serotype 61:k:1:5:(7)mentioning
confidence: 89%
“…Diarizonae serotype 61:k:1:5:(7) and the role of sheep in the transmission has been widely discussed [17,26,42], even though there have been no confirmed human cases associated with this specific serotype. In France, in 2008, a pseudo-outbreak in humans associated with SED was reported [43]. After a large number of SED positive samples from humans, trace-back investigations incriminated culture media containing contaminated sheep blood agar.…”
Section: Zoonotic Potential Of Salmonella Enterica Subsp Diarizonae Serotype 61:k:1:5:(7)mentioning
confidence: 99%
“…Clinical samples, laboratory equipment, stains and media may get contaminated and lead to pseudo-outbreaks. 19 One-time isolation of hitherto zoonotic pathogens may remain inconclusive. Positive isolates may not be associated with clinically manifest infection owing to muted immune response in premature neonates, elderly and immunocompromised patients.…”
Section: Attributing Pathogenicitymentioning
confidence: 99%